Design for Law Firm Innovation. A Case Study of the Innovation in Motion Awards in Baker McKenzie - Hagan, Margaret (RChD: creación y pensamiento, 2021)
Design and innovation methods have spread around the legal system as promising tools to reimagine how services are delivered, communications are done, and structured business models. This article explores how design thinking methods can be brought into a traditional law firm, like Baker McKenzie, through a mixture of design training, innovation sprints, and idea competitions. The case study shows how ideal design thinking methods must be adjusted for implementation in a law firm. Billable hour requirements, organizational hierarchy, and professional obligations can undermine design work. A first design round can snowball into more sprints, sabbaticals, and investment to grow lawyers’ capacity and the innovation’s development.